Mind-Object Identity: A Solution to the Hard Problem - Manzotti, Riccardo (Frontiers in Psychology, 2019)
Here I present a mind-object identity theory based on a straightforward hypothesis: One’s experience of an object is identical with the object itself. To defend this hypothesis, I will reconsider the notion of a physical object in terms of relative and actual properties, and in doing so, I will support a form of naturalism. The theory will also articulate two additional key hypotheses completely compatible with current standard physics: both physical objects and “the now” are recast in relative terms, as is routinely done with velocity.